Disaster Management in Jharkhand: A Case Study of Dhanbad District - Sanjay Kumar Jha1, Dr. K.K. Pathak2 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
With an eye toward the Dhanbad district, this research paper looks at disaster management strategies and issues facing Jharkhand, India. The study evaluates current disaster management systems and regulations, assesses the area's susceptibility to several natural and man-made hazards, and suggests ways to improve resilience. By use of a mixed-methods approach comprising qualitative interviews and quantitative data analysis, the study reveals important areas for development in disaster readiness, response, and recovery. The results underline the need for better early warning systems, programs for community-based disaster risk reduction, and more coordinated among stakeholders. Policymakers and professionals working on disaster management in comparable areas might benefit much from this case study of Dhanbad district.